Evidence and opportunities of hypothermia in acute ischemic stroke: Clinical trials of systemic versus selective hypothermia - Huber, Christian (Brain Circ, 2019)
Stroke is the second leading cause of death globally and the third leading cause disability. Acute ischemic stroke (AIS), resulting from occlusion of major vessels in the brain, accounts for approximately 87% of strokes. Despite this large majority, current treatment options for AIS are severely limited and available to only a small percentage of patients. Therapeutic hypothermia (TH) has been widely used for neuroprotection in the setting of global ischemia postcardiac arrest, and recent evidence suggests that hypothermia may be the neuroprotective agent that stroke patients desperately need. Several clinical trials using systemic or selective cooling for TH have been published, reporting the safety and feasibility of these methods. Here, we summarize the major clinical trials of TH for AIS and provide recommendations for future studies.